Postural dysregulation in systolic blood pressure is associated with worsened scoring on neurobehavioral function tests and leukoaraiosis in the older elderly living in a community. - Matsubayashi, K; Okumiya, K; Wada, T; Osaki, Y; Fujisawa, M; Doi, Y; Ozawa, T (Stroke (00392499), 1997)
Background and Purpose: Postural hypotension, which occurs frequently in community-living, apparently healthy elderly adults, is usually asymptomatic. However, the relation between postural changes in blood pressure and quantitative higher cerebral function or silent brain lesions remains unclear. We examined the association of exaggerated postural changes in systolic blood pressure with cognitive and quantitative neurobehavioral functions and with brain lesions on MRI in the community-dwelling older elderly.Methods: The study population consisted of 334 community-dwelling elderly adults, aged 75 years or older (mean age, 80 years). Postural changes in systolic blood pressure (SBP) were assessed using an autosphygmomanometer (BP-203 I). By the difference between the mean of two measurements of SBP at standing and at supine position (dSBP = SBP at upright-SBP at supine position), we divided the subjects into three groups: (1) 20 subjects with postural hypotension (d-SBP < or = -20 mm Hg), (2) 29 subjects with postural hypertension (dSBP > or = 20 mm Hg), and (3) 285 subjects with postural normotension (20 < dSBP < 20 mm Hg). We defined the former two groups as the postural dysregulation group. Scores in four neurobehavioral function tests (Mini-Mental State Exam. Hasegawa Dementia Scale Revised, computer-assisted visuospatial cognitive performance score, and the Up and Go Test) and activities of daily living were compared among the three groups. Brain lesions on MRI, including number of lacunes and periventricular hyperintense lesions, were compared among 15 age- and sex-matched control subjects with postural hypotension, 15 with postural hypertension, and 30 with postural normotension.Results: Twenty subjects (6.0%) exhibited postural hypotension and 29 (8.7%) postural hypertension. Scores in neurobehavioral functions and activities of daily living were significantly lower in the postural dysregulation group (both postural hypotension and hypertension groups) than in the postural normotension group. The postural dysregulation group exhibited significantly more advanced periventricular hyperintensities than the normotension group.Conclusions: Asymptomatic community dwelling elderly individuals with postural hypotension as well as those with postural hypertension had poorer scores on neurobehavioral function tests and more advanced leukoaraiosis demonstrated on MRI than those without exaggerated postural changes in SBP.